Excited to celebrate independence, UMP contingent wins merdeka parade - Nor Salwana, Mohammad Idris (2022)
PEKAN, 31 August 2022 – It was a proud moment when the contingent of Universiti Malaysia Pahang (UMP) comprising 32 staff was announced the winner of the Institute of Higher Education (IPT) category in the recent Pekan District 2022 National Day Parade competition.